Role of matrix protein in cytopathogenesis of vesicular stomatitis virus. - Blondel, D (1990)
The matrix (M) protein of vesicular stomatitis virus (VSV) plays an important structural role in viral assembly, and it also has a regulatory role in viral transcription. We demonstrate here that the M protein has an additional function. It causes visible cytopathic effects (CPE), as evidenced by the typical rounding of polygonal cells after VSV infection. We have analyzed a temperature-sensitive mutant of the M protein of VSV (tsG33) which is defective in viral assembly and which fails to cause morphological changes of the cells after infection at the nonpermissive temperature (40 degrees C). Interestingly, this defect in viral assembly as well as the CPE were reversible. Microinjection of antisense oligonucleotides which specifically inhibit M protein translation also inhibited the occurrence of CPE. Most importantly, when cells were transfected with a cDNA encoding the temperature-sensitive M protein of tsG33, no CPE was observed at the nonpermissive temperature. However, when these cells were shifted to the permissive temperature (32 degrees C), they rounded up and detached from the dish. These results demonstrate that M protein in the absence of the other viral proteins causes rounding of the cells, probably through a disorganization of the cytoskeleton. The absence of CPE at the nonpermissive temperature is correlated with an abnormal dotted staining pattern of M in these cells, suggesting that the mutant M protein may self-aggregate or associate with membranes rather than interact with cytoskeletal elements.